A new method for machinery fault diagnoses based on an optimal multiscale morphological filter - Tan, Wei (Strojniški vestnik, 2013)
In order to effectively eliminate the noise and extract the impulse components in the vibration signals, a new method based on an optimal multiscale morphological filter is proposed. In this method, firstly, the average of the closing and opening operator is used to construct the morphological filter, then the multiscale morphological filters structure elements (SEs) are optimized and selected using a particle swarm optimization algorithm (PSO). The noise in the original signal is filtered by the multiscale morphological filter. The proposed method was evaluated by simulated signals and bearing fault signals. The results show that the method can effectively filter the noise and extract the impulse characteristics of the vibration signals, which demonstrate the effectiveness of the proposed method.
Keywords: kotalni ležaji; multiscale morphological filter; noise reduction; optimizacijski algoritmi; optimization algorithm; razkrivanje značilnosti; structure element; strukturni elementi; večskalni morfološki filter; zmanjšanje šuma